2019
DOI: 10.1177/0033294119841846
|View full text |Cite
|
Sign up to set email alerts
|

“I Avenge; Others Aggress”: A Victim–Perpetrator Asymmetry in Judging Whether a Transgression Was Motivated by Revenge

Abstract: In two studies, victims differed from perpetrators as to whether they viewed a transgression as motivated by a desire for revenge. When participants wrote about autobiographical episodes in which they hurt others, they were somewhat likely to report that they were motivated by revenge; when the same participants wrote about episodes in which others hurt them, they were less likely to report that the perpetrators were motivated by revenge. This asymmetry could act as a barrier to reconciliation. This asymmetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Consequently, victims, relative to perpetrators, report perpetrators’ behaviors as being particularly harmful (e.g., Adams & Inesi, 2016; Baumeister, 1996; Elshout et al., 2017). Also, to minimize their blameworthiness, victims often downplay the legitimate reasons for the perpetrators’ aggressive behaviors, framing the aggression as not only harsh, but as incomprehensible and arbitrary as well (e.g., Baumeister et al., 1990; Ent & Parton, 2019). Even if victims experience an aggressive behavior as retaliation for a previous transgression (i.e., victims are the target of revenge), and are presumably worthy of at least some blame for the perpetrator’s’ reactions, they are motivated to report perpetrators’ retaliatory behavior as spiteful and disproportionate so as to look like the more harmed party in the ongoing dispute (e.g., Elshout et al., 2017; Stillwell et al., 2008).…”
Section: The Victim-perpetrator Asymmetrymentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, victims, relative to perpetrators, report perpetrators’ behaviors as being particularly harmful (e.g., Adams & Inesi, 2016; Baumeister, 1996; Elshout et al., 2017). Also, to minimize their blameworthiness, victims often downplay the legitimate reasons for the perpetrators’ aggressive behaviors, framing the aggression as not only harsh, but as incomprehensible and arbitrary as well (e.g., Baumeister et al., 1990; Ent & Parton, 2019). Even if victims experience an aggressive behavior as retaliation for a previous transgression (i.e., victims are the target of revenge), and are presumably worthy of at least some blame for the perpetrator’s’ reactions, they are motivated to report perpetrators’ retaliatory behavior as spiteful and disproportionate so as to look like the more harmed party in the ongoing dispute (e.g., Elshout et al., 2017; Stillwell et al., 2008).…”
Section: The Victim-perpetrator Asymmetrymentioning
confidence: 99%
“…Unlike victims, perpetrators would not benefit from sympathy or recompense by viewing their aggressive behavior as more harmful. Rather, perpetrators often report their aggressive behaviors as justified, legitimate, and proportionate responses to provocations (e.g., Elshout et al., 2017; Ent & Parton, 2019; Stillwell et al., 2008). In this way, perpetrators view their behaviors as “evening the score,”—any dispute they had with the victim is now settled—thus, victims would not be justified to retaliate further (e.g., Stillwell et al., 2008).…”
Section: The Victim-perpetrator Asymmetrymentioning
confidence: 99%
See 2 more Smart Citations
“…It is suggested that previous victimization activates a mechanism causing an individual to tend violate social norms [ 94 ]. Another mechanism contributing to the cycle of violence [ 95 ] may be motivation for revenge [ 25 , 96 ]. Research shows that individuals who are victims “are hypervigilant of potential threats from peers and interpret benign or innocuous stimuli as a threat, thereby increasing state-level anxiety” [ 97 ].…”
Section: Introductionmentioning
confidence: 99%